FINANCIAL DISTRESS TERHADAP PRAKTIK MANAJEMEN LABA DAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI DI MASA PANDEMI COVID-19 - Dewi Ayu Mellennia; Khomsiyah (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2023)
The purposes of this investigation is to examines the results of financial distress to earnings management practices, good corporate governance to earnings management practices, with good corporate governance as a moderating variable of influence financial distress to earnings management practices. This research uses a 33 samples of companies listed on the and including the CG score in their annual reports during 2019 to 2021. Purposive sampling method is the technique used in data collection. The method used in this study is a quantitative method, while the analytical tool uses E-views 12. The results of this research indicates that financial distress has a positive effects significant on earnings management practices, good corporate governance has not a negative effects on earnings management practices, while the implementation of corporate governance does weaken the influence of financial distress on earnings management. The implications of this research results for investors to provide information about the condition of the company's financial health so that it can assist in making the right decisions regarding the investment to be made to obtain maximum profits.